PENGARUH PELAYANAN AREA TRAFFIC CONTROL SYSTEM (ATCS) TERHADAP KEPUASAN PENGGUNA JALAN DI KOTA DENPASAR: PENGARUH PELAYANAN AREA TRAFFIC CONTROL SYSTEM (ATCS) TERHADAP KEPUASAN PENGGUNA JALAN DI KOTA DENPASAR - Putri Anggreni (Forum Manajemen, 2018)
The purpose of this study are: (1) To determine the effect of service qualityArea Traffic Control System (ATCS) to the satisfaction of road users in Denpasar; (2)To determine the relationship of service quality Area Traffic Control System (ATCS)to the satisfaction of road users in the city of Denpasar.The method used in thisstudy is a quantitative method that is supported by the literature study, observationand interviews. Data collection techniques used were through questionnaires.In this study, a population that drivers of the technical implementation unit ofthe ground transportation service of the denomination of the city the technicalimplementation unit of the ground transportation service of the denomination of thecity of of Denpasar used as a source of data used and the sample of 40 respondents. To analyze the problem and the hypothesis then used simple of linear regression analysis using SPSS. The results of testing the hypothesis, concluding that thetraffic services effect on drivers satisfaction at the technical implementation unitof the ground transportation service of the denomination of the city of Denpasar asevidenced with the Sig F 0.000 <Î± = 0.05 level. While the impact strong correlationthat significantly effect satisfaction on customer at the technical implementation unitof the ground transportation service of the denomination of the city of Denpasar.